1988
DOI: 10.1007/bf00974080
|View full text |Cite
|
Sign up to set email alerts
|

Upper GI examinations in older premature infants with persistent apnea: correlation with simultaneous cardiorespiratory monitoring

Abstract: Upper gastrointestinal examinations with simultaneous cardiorespiratory monitoring were performed in 39 older premature infants with persistent apnea. Swallowing incoordination was documented to be causatively related to persistent apnea in such infants, especially with feeding. Direct relationship between apnea and gastroesophageal reflux was not documented in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…[29] It is associated not only with apnea, but also with choking and history of pneumonia in infants. [30][31][32] Although none of the 7 infants with nasopharyngeal refl ux in our study showed laryngeal penetration or aspiration, the potential for aspiration might be underestimated.…”
Section: Discussionmentioning
confidence: 69%
“…[29] It is associated not only with apnea, but also with choking and history of pneumonia in infants. [30][31][32] Although none of the 7 infants with nasopharyngeal refl ux in our study showed laryngeal penetration or aspiration, the potential for aspiration might be underestimated.…”
Section: Discussionmentioning
confidence: 69%
“…6 Nasopharyngeal reflux has been associated with apnea, choking, and a history of pneumonia in the infant. [7][8][9] Preterm infants who were nursed in the head-elevated tilt position, altering swallowing function, were found to have significantly fewer brady-cardic or hypoxemic episodes when compared with a horizontal position. 10 Despite the strength of the relationship between dysphagia and respiratory complications, there is little understanding of the biomechanics of infant dysphagia.…”
mentioning
confidence: 99%
“…6 Nasopharyngeal reflux has been associated with apnea, choking, and a history of pneumonia in the infant. [7][8][9] Preterm infants who were nursed in the head-elevated tilt position, altering swallowing function, were found to have significantly fewer bradyFrom *Otolaryngology-Head and Neck Surgery and ‡Department of Pediatrics, …”
mentioning
confidence: 99%
“…5 With videofluoroscopy, it has been demonstrated that apnea and bradycardia occurred during retention of barium in the hypopharynx and/or nasopharyngeal backflow. [6][7][8] Therefore, any premature or term infant who has difficulty feeding and/or has experienced apnea, bradycardia, cyanosis, or a near-miss sudden infant death syndrome episode should be evaluated for dysphagia.…”
Section: Identifying Infants and Children With Dysphagiamentioning
confidence: 99%